Study Effect of Salt Washing Process on Content and Iodium Stability of Salt - Saksono, Nelson (Makara Journal of Technology, 2002)
Effect of Salt Washing Process on Content and Iodium Stability of Salt. Salt washing process should increase the salt quality. It should clean the salt from sludge or clay and also reduce the impurity compound such as Mg, Ca and the reductor content. The objective of these reseach is to assess the effect of washing process on the content og hygroscopic impurities compound (Ca and Mg), and reductor content of salt. The research also investigate the water absorbing, pH, KIO3 content as function of time to obtain effect of washing process on KIO3 stability in salt. The experiment result shows that the lowest content of Mg and reductor compound 0.016 % wt and 2.65 ppm respectively which is reached at the fi ne salt washing process using 27 % wt brine. The analysis of water content indicates an increase the Ca and Mg content, causing an water absorbtion in salt , However the effect on pH the is not clear.